The practice of enterprise modeling : 9th IFIP WG 8.1. Working Conference, PoEM 2016, Skövde, Sweden, November 8-10, 2016, Proceedings /: 9th IFIP WG 8.1. Working Conference, PoEM 2016, Skövde, Sweden, November 8-10, 2016, Proceedings. (2016) - Unknown
No abstract available